FOR A CLASS OF LINEAR OPERATORS - Malčeski, Aleksa (Matematichki Bilten, 2006)
\(X\) is a normed and 2-normed space when norm and 2-norm are associated with the non-equation \(x,y Vert ≤ Kx Verty Vert\). A class of linear operators from \(x\) to \(B(x)\) is given.